Dihydroartemisinin Increases the Sensitivity of Photodynamic Therapy Via NF-κB/HIF-1α/VEGF Pathway in Esophageal Cancer Cell in vitro and in vivo - Yanjing Li (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Although photodynamic therapy (PDT) can relieve esophageal obstruction and prolong survival time of patients with esophageal cancer, it can induce nuclear factor-kappa B (NF-κB) activation in many cancers, which plays a negative role in PDT. Dihydroartemisinin (DHA), the most potent artemisinin derivative, can enhance the effect of PDT on esophageal cancer cells. However, the mechanism is still unclear. Methods: We generated stable cell lines expressing the super-repressor form of the NF-κB inhibitor IκBα and cell lines with lentivirus vector-mediated silencing of the HIF-1α gene. Esophageal xenograft tumors were created by subcutaneous injection of Eca109 cells into BALB/c nude mice. Four treatment groups were analyzed: a control group, photosensitizer alone group, light alone group, and PDT group. NF-κB expression was detected by an electrophoretic mobility shift assay, hypoxia-inducible factor α (HIF-1α) and vascular endothelial growth factor (VEGF) by real-time PCR, NF-κB, HIF-1α, and VEGF protein by western blot, and Ki-67, HIF-1α, VEGF, and NF-κB protein by immunohistochemistry. Results: PDT increased NF-κB activity and the gene expression of HIF-1α and VEGF in vitro and in vivo. In contrast, the DHA groups, particularly the combined DHA and PDT treatment group, abolished the effect. The combined treatment significantly inhibited tumor growth in vitro and in vivo. NF-κB activity and HIF-1α expression were also reduced in the stable IκBα expression group, whereas the former showed no change in HIF-1α-silenced cells. Conclusion: DHA might increase the sensitivity of esophageal cancer cells to PDT by inhibiting the NF-κB/HIF-1α/VEGF pathway.